The Influence of Corporate Governance on E-Commerce Company Performance in the Artificial Intelligence Era: JEL Classification: G34, L81, O33, M15, D22 - John Mathew Reyes; Maria Angla Cruz (Mustard Journal De Ecobusin, 2026)
This study investigates the influence of corporate governance on the performance of e-commerce companies in the Philippines in the era of Artificial Intelligence (AI). The rapid development of AI technologies has transformed digital business operations, increasing the importance of governance mechanisms in ensuring organizational effectiveness, accountability, and competitiveness. This research employed a quantitative explanatory approach using survey data collected from managers and executives working in Philippine e-commerce companies. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that corporate governance has a positive and significant effect on company performance. Governance dimensions such as transparency, accountability, board effectiveness, risk management, and stakeholder protection were found to contribute substantially to operational efficiency, innovation capability, financial growth, and competitive advantage. The study also demonstrates that governance quality plays an important role in supporting organizational adaptability within AI-driven business environments. The research contributes theoretically to governance and digital transformation literature while providing practical implications for managers and policymakers seeking to strengthen governance frameworks and organizational sustainability in the digital era.